Kurds in Volume Five of the Book (History of Erbil): (Ebn Al-Mustawfy 637 H / 1239 M) - فرج قاسم محمد (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
The book “History of Erbil” is considered to be one of the original historic sources of the mid-centuries (13th century/ 7th Hijri) Islamic history. The book comprised of five volumes, the first two of which have been identified and verified by (Sami Bn Al-said Khamas Saqar). Researchers in the field believed that these two volumes were the only survived ones, but later the fifth volume of the book was found in the National Museum of Tunisia under the title “Andalusian Poets”. After identification and versification, it was concluded that the manuscript is not about Andalusian Poets but it is the fifth volume of the book “History of Erbil” which is about 334 poets in and around Erbil. The objective of this research is to present the lives and influences of many Kurdish characters, poets and scientists who are mentioned in the book. Moreover, this research presents a number of writers and characters who are not mentioned before which is valuable to Kurdish history. The authors use historic, descriptive and analytical methodologies in the research and in some places, comparative methodology is used to compare the findings with historic books in the same century.